Acute ischemic stroke due to unruptured small aneurysm of internal carotid artery: A case report. Issue 41 (9th October 2020) - Su, Hongjun; Zhao, Na; Zhao, Kun; Zhang, Xuejuan; Zhao, Riguang
Abstract: Rationale: Intracranial small aneurysm is a rare cause of ischemic stroke, and been described only in sparse case reports. The exact pathophysiology, treatment strategies, and prognosis remain incompletely understood. Patient concerns: A 42-year-old man presented with an acute onset weakness of the right limbs. Diagnoses: Neuroimaging evaluation confirmed a diagnosis of acute ischemic stroke and left internal carotid artery (ICA) small aneurysm. Interventions: The patient underwent oral anti-platelet therapy (100 mg aspirin daily). Outcomes: The patient recovered to normal status within 4 weeks following antiplatelet treatment. During a follow-up period of 1 year, he remained neurologically asymptomatic and led a virtually normal life. Lessons: It is crucial for clinicians to be aware of this entity, as cerebral infarction caused by small cerebral aneurysm is extremely rare.